A bibliometric analysis of immersive environments in STEM education: Global trends, research structure, and thematic evolution - Phonrawatjaradwat, Sutidan; Jantakoon, Thada; Laoha, Rukthin (Edelweiss Applied Science and Technology, 2025)
This study presents a comprehensive bibliometric analysis of immersive environments in STEM education, examining global research trends, intellectual structures, and thematic developments within the field. Using a dataset of 100 Scopus-indexed publications screened through PRISMA procedures, the analysis employed performance indicators, citation metrics, co-occurrence networks, and thematic mapping to evaluate the evolution of immersive technologies, including VR, AR, MR, and XR in STEM learning contexts. The results reveal a steady increase in annual scientific production, highlighting the growing integration of immersive tools to enhance engagement, conceptual understanding, and experiential learning in science and engineering education. Key research clusters emphasize simulation-based learning, virtual laboratories, and engineering applications, while foundational themes such as VR/AR for student learning remain conceptually broad and require further theoretical refinement. Geographic patterns indicate strong contributions from technologically advanced countries, with emerging participation from diverse regions. The thematic map identifies well-developed motor themes alongside emerging areas such as personalized immersive training and early-stage metaverse applications. Overall, the findings demonstrate that immersive technologies have transitioned from experimental innovations to influential components of modern STEM pedagogy. Future research should strengthen theoretical integration, methodological rigor, and equitable access to immersive learning ecosystems to fully realize their transformative potential in STEM education.